2019
DOI: 10.1177/1363461519858446
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms and perceived mental health changes after a livelihood intervention for HIV-positive Kenyans: Longitudinal, qualitative findings

Abstract: While food insecurity and poverty worsen mental health outcomes among people living with HIV/AIDS (PLHIV), few intervention studies have targeted poverty and food insecurity as a way to improve mental health. Among HIV-positive patients, addressing such upstream determinants may prove crucial to ensure better mental health and HIV clinical outcomes. We integrated longitudinal, qualitative research into a randomized trial of a livelihood intervention to understand processes and mechanisms for how the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Gender inequality and rural-urban differences in access to job opportunities further add to the growing problem of unemployment and livelihood struggles for the marginalized populations [ 12 ]. Research on such evidence-based integrated health and livelihood development interventions informed the conceptual model of our intervention (Figure 1) [ 13,14 ]. The conceptual model informed that peer-led education sessions with beneficiaries would help in bringing behaviour change in the society together with mobilization of the communities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gender inequality and rural-urban differences in access to job opportunities further add to the growing problem of unemployment and livelihood struggles for the marginalized populations [ 12 ]. Research on such evidence-based integrated health and livelihood development interventions informed the conceptual model of our intervention (Figure 1) [ 13,14 ]. The conceptual model informed that peer-led education sessions with beneficiaries would help in bringing behaviour change in the society together with mobilization of the communities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found an improvement in food security, CD4 count, and rates of viral suppression after 1 year. Companion qualitative studies suggested additional beneficial impacts on stigma and mental health [ 21 , 22 ]. In addition to social protection and poverty reduction programs, standardized assessments capable of distinguishing relative impoverishment should be incorporated into routine clinical care for HIV in order to identify patients at highest risk of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This special issue of Transcultural Psychiatry provides a snapshot of current interdisciplinary work that reflects the complexity and ongoing evolution of GMH. The authors reflect on the histories and colonial legacies of violence inscribed in mental suffering and programming (Capella, Jadhav, & Moncrieff, 2020; Hickling, 2020; Ortega & Wenceslau, 2020), on current models of culturally responsive intervention and implementation (Bustamante Ugarte et al., 2020; Hatcher et al., 2020; Honikman, Field, & Cooper, 2020; Mascayano et al., 2020; Shehadeh et al., 2020; Verhey et al., 2020) and on the challenges to mental well-being from the impending conditions of catastrophic climate change (White, 2020). Another set of contributions challenge established narratives on psychological suffering and trauma after war (Medeiros, Nanicha Shrestha, Gaire, & Orr, 2020), natural disaster (Newnham et al., 2020), and cultural practices of female genital cutting (Omigbodun, 2020).…”
Section: Moving Beyond a Polarized Debatementioning
confidence: 99%
“…While Lund and colleagues’ initial review was inconclusive, they noted there was greater empirical support for the “social drift” hypothesis. Recent evidence, however, provides further support for the “social causation” hypothesis, such as Hatcher and colleagues’ (2020) article in this issue on the improvement of mental health outcomes in Kenya through a livelihood intervention that provided HIV-positive and food-insecure people with an irrigation pump, farming training, and micro-loans. The interviews conducted before and after the interventions found improvements in participants’ mental health experienced as reduced stress, lessened anxiety, improved mood, fewer symptoms of depression, and a more hopeful outlook on the future.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%